2001
DOI: 10.1095/biolreprod64.4.1165
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Heparin/Heparan Sulfate Interacting Protein/Ribosomal Protein L29 During the Estrous Cycle and Early Pregnancy in the Mouse1

Abstract: Using a variety of approaches, we have examined the expression of the heparin/heparan sulfate (Hp/HS) interacting protein/ribosomal protein L29 (HIP/RPL29) in mouse uteri during the estrous cycle and early pregnancy. HIP/RPL29 selectively binds heparin and HS and may promote HS-dependent embryo adhesion. HIP/RPL29 was prominently expressed in both luminal and glandular epithelia under almost all conditions, including the phase of embryo attachment. In contrast, differences were noted in HIP/RPL29 expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…PMEFs cells were collected by direct solubilization in SEB to which phosphatase inhibitor cocktail (Calbiochem) was added. Protein samples were quantified using a standard Lowry assay (Lowry et al, 1951), and protein lysates of equal amount (10 -20 g) were combined to an equal volume of 2ϫ Laemmli buffer and submitted to 10% (w/v) SDS-PAGE as described (Julian et al, 2001). After transfer to a nitrocellulose membrane, the blot was blocked in blocking buffer (5% [w/v] BSA, 0.1% [v/v] Tween-20 in PBS) for at least 6 hr and probed with specific antibodies raised in rabbit.…”
Section: Sds-page and Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…PMEFs cells were collected by direct solubilization in SEB to which phosphatase inhibitor cocktail (Calbiochem) was added. Protein samples were quantified using a standard Lowry assay (Lowry et al, 1951), and protein lysates of equal amount (10 -20 g) were combined to an equal volume of 2ϫ Laemmli buffer and submitted to 10% (w/v) SDS-PAGE as described (Julian et al, 2001). After transfer to a nitrocellulose membrane, the blot was blocked in blocking buffer (5% [w/v] BSA, 0.1% [v/v] Tween-20 in PBS) for at least 6 hr and probed with specific antibodies raised in rabbit.…”
Section: Sds-page and Western Blottingmentioning
confidence: 99%
“…In contrast to adult tissues, HIP/ RPL29 displays a much more widespread pattern of expression throughout embryonic development, and high levels of HIP/RPL29 are found in all developing organs (Kirn-Safran et al, 2000;Julian et al, 2001). Of interest, several reports showed that HIP/ RPL29 expression is up-regulated in human carcinomas and constitutes a candidate marker for abnormal growth when overexpressed (de Nigris et al, 1998;Wang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…HIP/RPL29 is prominently expressed in uterine luminal and glandular epithelia in both humans and mice at all stages of the cycle including during the window of receptivity [32,34]. During the post-implantation period in mice, HIP/RPL29 accumulates in decidualizing stroma and actively dividing embryonic structures [34]. These expression patterns suggest an important role for HIP/RPL29 in the establishment and maintenance of pregnancy.…”
Section: Hip/rpl29mentioning
confidence: 98%
“…HIP RL29 also can modulate blood coagulation processes [33] and inhibits heparanase activity (see below). HIP/RPL29 is prominently expressed in uterine luminal and glandular epithelia in both humans and mice at all stages of the cycle including during the window of receptivity [32,34]. During the post-implantation period in mice, HIP/RPL29 accumulates in decidualizing stroma and actively dividing embryonic structures [34].…”
Section: Hip/rpl29mentioning
confidence: 99%
See 1 more Smart Citation